PANCASILA DALAM IKLAN TELEVISI - Rika Lusri Virga (Profetik: Jurnal Komunikasi, 2014)
In 2004, SidoMuncul intensively uses television advertising. One version of the ad is very interesting which is Kuku Bima EnerG with Maluku version. In herbal medicine company, advertising displays some celebrities and athletes from Indonesia. Beautiful view of the sea and historical relics owned by Maluku, so the commercials do various activities with the local people. Start by playing the ball, diving for pearls as well as helping anglers on the beach. In this ad also displays a scene where the commercials come to Monumen Gong perdamaian in Maluku. In another scenes shows a young couple who know each other deeply despite having different beliefs. From this background, researcher interested to see how the discourse of Indonesian unity as in the third precept of Pancasila that shows in the ad. Through Fairclough discourse analysis there are three stages of analysis. Text analysis, analysis of discourse practice and sociocultural practice analysis. However, in this study has only discussed how the discourse of unity values on the third precept to only reached the first stage, text analysis. In the analysis it was found that the representation of the value of Indonesian unity through the text displayed in the form of an image showed young man and woman with differences in belief but still has relationship.